Case report: Orthostatic leg tremor as the initial manifestation in a patient with metabotropic glutamate receptor-5 encephalitis without cortical dysfunction: complexities in identification and treatment - Yang, Xia; Liu, Qiong; Lai, Ming-feng; Ma, Xiao-hong; Hao, Xiao-ting; Xu, Jia-jun; Guo, Wan-jun (Frontiers in Neurology, 2023)
Objective Metabotropic glutamate receptor 5 (mGluR5) encephalitis is such a rare type of autoimmune encephalitis that its diagnosis remains a challenge. Case report A 19-year-old female patient initially presented with anxiety and orthostatic leg tremors without cortical dysfunction. We found that this patient was positive for mGluR5 antibodies in both serum (1:1,000) and cerebrospinal fluid (1:32). After comprehensive intervention, the patient showed complete recovery at the 18-month follow-up. Discussion This report expands our knowledge of the possible presentations of mGluR5 encephalitis for early diagnosis, which makes it possible to prevent serious consequences and improve the prognosis.